Rozwój zrównoważony w perspektywie deontologicznej - Płachciak, Adam; Mukarutesi, Dative (Annales. Etyka w Życiu Gospodarczym, 2020)
The idea of sustainable development as a normative concept emphasizes the necessity for a wider consensus on meeting human needs, ensuring social equity, and respecting planetary boundaries. The purpose of the article focuses on the deontological orientation in perceiving sustainable development. It is expected that looking at sustainability from the deontological perspective might increase individuals’ awareness of responsibility towards respecting the needs of the world’s poor, environmental boundaries, and moral equity, which emphasizes that all people are equal. Any attempt to achieve sustainability demands, first of all, rational action placed on moral duties/obligations before individual people or institutions can achieve their particular desires and goals. According to this perspective, sustainability should be treated as a prior constraint in obtaining economic maximization.